The Measurement of the Effectiveness of Zakat Disbursement in Indonesia - Bahri, Efri Syamsul; Utama, Indra (Institut Agama Islam Negeri Madura, 2021)
According to Law No. 23 of 2011, Indonesia's zakat management is carried out by 572 entities, consisting of the National Zakat Agency (known as Baznas), Baznas Province, Baznas Regency/City, and Amil Zakat Institution (known as LAZ). One of the purposes of zakat management is to increase the effectiveness in managing zakat. The collection of zakat nationally in 2015-2019 grew 180%, with an average of IDR 6.65 trillion per year. Furthermore, disbursement in 2015-2019 grew 286% with an average of IDR 5.11 trillion. This study measures the effectiveness of zakat disbursement to describe the capacity in channeling zakat. Data sources were obtained from the National Zakat Statistics for the period 2015-2019. Data analysis by using the formula of the allocation to collection ratio adopted from the zakat core principles. The study results found that the effectiveness of zakat disbursement reached 77% in the Effective category. The highest achievement in 2019 was 85%. LAZ reached the highest level with the Very Effective category (94%). The suggestion is that the effectiveness of zakat disbursement needs to be continuously improved to achieve the Very Effective category. Thus, the purpose of zakat management can be achieved.